Approaching labour : the 'events' that women experience in the last two weeks of pregnancy : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Midwifery at Massey University - Gunn, Jacqueline (Massey University, 2001)
The 'everyday' events that women experience in the final fortnight of pregnancy as their bodies prepare for labour, is not well reported in the research. This preliminary' descriptive study was designed to answer the question: are there specific events in late pregnancy that are associated with the onset of labour? One hundred and nineteen women used the daily diary that was specifically developed for the study. They recorded the events they experienced between 38 weeks gestation and the onset of their labour. Women were eligible to participate if they had an uncomplicated singleton pregnancy, and were cared for by an independent midwife. Fifteen events were identified that women either commonly experienced or that were important for individual women. These were: cervical 'needling' sensations, fluctuation in fetal movements, uterine activity, mood and energy fluctuations, broken sleep, disturbed bowel and bladder patterns, alterations to vaginal secretions, appetite and mood, nesting/deadline urges, raised libido and enhanced sense of smell and hearing acuity. The study results do not demonstrate any statistically significant relationships between any of the variables with the onset of labour. However, clinically significant frequencies and patterns have been identified for cervical' needling sensations, fluctuations in fetal movements, uterine activity, a 'show', disturbances to bowel activity, mood lability and broken sleep. The study findings provide evidence for the patterns of occurrence of these events that, apart from uterine activity and broken sleep, have hitherto rested on anecdotal, traditional information rather than research. Specific findings from the study indicate that in the final two weeks of pregnancy, cervical needling sensations were experienced by 74% of the study sample that may mirror the physiological process of cervical softening or effacement. A 'normal' range of fetal movement variation that is not associated with fetal compromise was experienced by 79% of the study participants. Half of the study population experienced mood fluctuations in the fifteen days preceding the onset of labour, whilst two thirds of the sample did not experience a 'show' before the onset of labour. Several events such as broken sleep and disturbances of bowel activity occur in more complex patterns and over a longer period than is commonly reported in the literature examined for this study. Midwives help women to stay calm and confident about childbirth by sharing information that can enable each woman to anticipate the normal experiences of childbirth. Providing such 'anticipatory information' is a key midwifery activity. The results of this study provide evidence for the 'anticipatory information ' related to the final weeks of pregnancy that midwives share with women. Multiple questions for further research have been generated by the study. In particular, seven events occurred in a synchronous pattern six days prior to the onset of labour, and three of the four post-dates multigravidae whose babies were in an occipito-posterior position at the onset of labour had an operative outcome. These interesting findings need further study to determine whether the findings have significance.
Keywords: Pregnancy; Trimester, Third -- Case studies; Midwifery